Damage characteristics and failure mechanism analysis of NEPE propellant at high strain rates - Zhengwei Sun; Jinsheng Xu; Changsheng Zhou; Xiong Chen; Zongtao Guo; Qixuan Song (Scientific Reports)
Abstract The study of mechanical properties and failure mechanism of propellants under impact loads is crucial for analyzing structural integrity of propellant charges. An experimental investigation was conducted on NEPE propellant using a separated Hopkinson pressure bar to conduct high strain rate uniaxial impact tests. Deformation and failure processes of the propellant under impact conditions were recorded with a high-speed camera. The microscopic failure forms of the propellants were observed using a scanning electron microscope and an optical microscope. Stress-strain curves and high-speed images revealed that the damage behavior and failure mechanism of NEPE propellants are significantly influenced by strain rate. As the strain rate increases, there is a notable increase in the deformation degree of the propellant specimens, with a more pronounced shear effect. This leads to an earlier occurrence of failure and a more severe degree of failure. The predominant failure forms observed in NEPE propellants include transgranular failure, matrix tearing, and cavity merging. A nonlinear visco-hyperelastic constitutive model with damage at high strain rates was established to provide a precise account of the mechanical response of NEPE propellant under high strain rates.